Effect of Abnormal Degree of Fiber Cross-section on the Moisture-Transfer and Dry-fast Properties of Knitted Fabric (Journal of Fiber Bioengineering and Informatics, 2010)
With the help of electronic microscope and scanning electronic microscope, profiled polyesterfibers with cross section shapes like “Y”, “+” and “C” were analyzed individually. Four kinds of single anddouble-faced knitted fabrics with different structures and density were manufactured with the profiledpolyester fibers, and their wicking height, water retention and drying efficiency were investigatedindividually. It was found that the more abnormal the fiber cross section is, the better is the moisture-transferand fast drying properties of its fabrics.
Keywords: Profiled fiber; abnormal degree of the fiber cross sections; wicking property; water retention; drying efficiency